How Do Passive Margins Convert to Active Margins? - Timothy M. Kusky; Junpeng Wang (Geochemistry, Geophysics, Geosystems)
Abstract There has been a long debate about how passive (Atlantic‐type) margins can convert to active (Andean) margins, particularly if they can do so directly, or some other process such as an arc‐continent collision must intervene (Burke et al., 1984; Dewey, 1969, https://doi.org/10.1016/0012‐821x(69)90089‐2; Kusky & Kidd, 1985). Most numerical models have long‐suggested that only very young passive margins can be sites of subduction initiation since old margins become stronger as they cool and develop thick sedimentary piles during thermal subsidence (e.g., Cloetingh et al., 1982, https://doi.org/10.1038/297139a0, 1989, https://doi.org/10.1007/bf00874622; 1996; Zhong & Li, 2019, https://doi.org/10.1029/2019gl084022), whereas other analog and numerical models have suggested that old passive margins may spontaneously convert to subduction zones (e.g., Bercovici & Mulyukova, 2021, https://doi.org/10.1073/pnas.2011247118; Faccenna et al., 1999, https://doi.org/10.1029/1998jb900072; Nikolaeva et al., 2010, https://doi.org/10.1029/2009jb00654; Stern & Gerya, 2018, https://doi.org/10.1016/j.tecto.2017.10.014; Zhang et al., 2023, https://doi.org/10.1029/2023gl103553).